2010
DOI: 10.1111/j.1530-0277.2010.01222.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Expectancies and Drinking Refusal Self‐Efficacy Mediate the Association of Impulsivity With Alcohol Misuse

Abstract: The hypothesized model was confirmed on a large sample of young adults and replicated on a sample of treatment-seeking substance abusers. Taken together, these findings shed further light on the mechanisms through which an impulsive temperament may convey risk for alcohol misuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
122
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(141 citation statements)
references
References 97 publications
14
122
2
3
Order By: Relevance
“…Factor analytic studies have shown psychoticism to load with other measures of rash impulsiveness, supporting its construct validity Gullo et al, 2010;Zelenski & Larsen, 1999). The short-form psychoticism scale has a 2-year test-retest reliability of .61 -.72 (Heath, Cloninger, & Martin, 1994).…”
Section: Impulsivitymentioning
confidence: 99%
See 4 more Smart Citations
“…Factor analytic studies have shown psychoticism to load with other measures of rash impulsiveness, supporting its construct validity Gullo et al, 2010;Zelenski & Larsen, 1999). The short-form psychoticism scale has a 2-year test-retest reliability of .61 -.72 (Heath, Cloninger, & Martin, 1994).…”
Section: Impulsivitymentioning
confidence: 99%
“…Impulsive drinkers hold different beliefs about alcohol compared to non-impulsive drinkers, believing it to be both more rewarding and more difficult to resist (Gullo, Dawe, Kambouropoulos, Staiger, & Jackson, 2010). Indeed, mediational analyses have demonstrated that the influence of impulsivity on alcohol use is mediated, in part, through cognition (Gullo et al, 2010;Kabbani & Kambouropoulos, 2013;Leeman et al, 2012), although these have mostly been with non-dependent college drinkers.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations